IMPLEMENTATION OF TRI HITA KARANA VALUES FOR FORMING STUDENT’S CLEAN AND HEALTHY LIVING BEHAVIOR - I Made Mahaardhika; Gusti Apriani Utari (Indonesian Journal of Educational Development (IJED), 2023)
The purpose of writing this class action research is to determine whether group counseling services can improve the Implementation of Tri Hita Karana values to form clean and healthy living behavior in Grade VII Students E, at SMP Negeri 9 Denpasar. The object of this research is Class VII students E, at SMP Negeri 9 Denpasar with eight students who were given group guidance services consisting of 5 male and 3 female students. In analyzing the data of this study, the researcher used a percentage descriptive analysis technique to describe the implementation level of Tri Hita Karana values to Form Clean and Healthy Living Behavior of Students before (pre-test) and after (post-test) given treatment in the form of Group Guidance Services. The results obtained from this study show group guidance services can improve the implementation of the values of Tri Hita Karana to form student Clean and Healthy Living Behavior as evidenced by the results of the initial conditions/before service by 55% with the highest percentage value being 65%, in cycle I, it increased to 69 % with the highest percentage value was 77%, and in cycle II, it increased again with an average of 83% with the highest percentage value being 90%. After analyzing these results using percentage descriptive analysis, it was concluded that group guidance services could improve the implementation of the Tri Hita Karana to form students' Clean and Healthy living Behavior.